1989
DOI: 10.1111/j.1365-2133.1989.tb08190.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratum corneum hydration and amino acid content in xerotic skin

Abstract: The relationship between clinical severity, the hydration state of the skin surface as assessed by a conductance with a 3.5 MHz high frequency impedance meter, and the amino acid content of the stratum corneum (SC) of six patients with ichthyosis vulgaris and 30 elderly persons with varying degrees of xerosis was investigated. With an increase in the severity of xerosis the SC showed a decrease in hydration and in its extractable amino acid content. There was a significant correlation between the hydration sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(151 citation statements)
references
References 7 publications
2
147
0
2
Order By: Relevance
“…Filaggrin is a source of NMFs, which are essential for skin hydration and barrier function (19,20). Genetic studies have shown that loss-of-function mutations in FLG, the human gene encoding profilaggrin and filaggrin, are a major risk factor for the development of atopic dermatitis (AD) (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Filaggrin is a source of NMFs, which are essential for skin hydration and barrier function (19,20). Genetic studies have shown that loss-of-function mutations in FLG, the human gene encoding profilaggrin and filaggrin, are a major risk factor for the development of atopic dermatitis (AD) (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this mutation, lower levels of NMF are generated in atopic skin and this is thought to contribute to an impaired barrier function (4,11). Furthermore, a reduced NMF level has also been reported in other abnormal dry and scaly skin conditions (12)(13)(14). Therefore, measuring the amount of NMF in the skin may offer a useful indicator of skin hydration and be helpful in the early diagnosis of these skin disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid content of the samples attached to the Cello tape (Nichiban, Tokyo) was measured after disolving in toluene according to the method previously described by Horii et al (1989). …”
Section: Function Of the Stratum Corneummentioning
confidence: 99%